Influence of rectangular micro inserts and micro chambers heat transfer characteristics of microchannel heat exchanger - Kuruva Krishna Murthy; K Vijaya Kumar Reddy; Abdul Saddique Shaik; Irfan Anjum Badruddin; Sarfaraz Kamangar; Muhammad Nasir Bashir; Muhammad Mahmood Ali (Case Studies in Thermal Engineering)
This decade's smaller gadgets have made heat removal in electronics and microprocessors increasingly crucial necessitating the use of micro channel heat exchangers (MCHEs). The current study investigates the MCHE performance improvement through micro chambers and rectangular inserts with varying orientations (angle of insert: 0°, 45°, and 90°). Experimental and numerical studies are conducted in a laminar environment, with Reynolds number varying from 74 to 446. Simulation of fluid flow and heat transfer is accomplished through Finite Volume Method. Thermal performance indicators, fluid flow parameters, pressure drop, friction factor, are used to evaluate and quantify the efficiency of MCHEs. It is shown that inserting two rectangles at 90° angle can achieve the ideal heat transfer coefficient. As a result, compared to the MCHE-MCDCI with various orientations of 0°, 45°, and 90°, respectively, the increase in Nu is 12.21 %, 23.42 %, and 37.10 %, respectively. The rectangular insert at an angle of 90 in an MCHE caused the highest pressure loss. In contrast with MCHE-MCDCI. The pressure drop at 0°, 45°, and 90° increases by 13.26 %, 37.94 %, and 52.70 %, respectively. When compared with double cylindrical inserts, MCHEs with rectangular inserts that are orientated at an angle of 90° produced the greatest PEC.